Valuing and Capital Structure Analysis of PT. Menara Sumberdaya Indonesia - Muharam, Barkah; Sukarno, Subiakto (Journal of Business and Management, 2015)
Abstract. Indonesia as the fourth largest country in the world has high population and domestic consumption. This condition is highly beneficial for industry in Indonesia. Milk and dairy product is one of them. Fortunately this industry still dominated by foreign company and importer to support local demand. This condition showed that the local producers still uncultivated huge opportunity in local market. PT. Menara Sumberdaya Indonesia (MSI) as one of the local producers saw this condition as opportunity. However MSI need a new machine to support the expansion, because the current production capacity is already at maximum. Therefore MSI need external capital to fund the expansion. This study aims to give recommendation with calculation about capital structure and company valuation to MSI management to get funding strategy. Based on the calculation it shows MSI need to get the external fund from both debt and equity financing to fund the expansion, in order to obtain optimal capital structure. MSI also suggested increasing the volume of production to reduce the idle capacity of the new machine.Â Keywords: Valuation, discounted cash flow, acquisition, optimal capital structure